Effect of Cyanide Ligands on the Electronic Structure of [FeFe] Hydrogenase Active‐Site Model Complexes with an Azadithiolate Cofactor. Issue 43 (13th September 2013) - Erdem, Özlen F.; Stein, Matthias; Kaur‐Ghumaan, Sandeep; Reijerse, Edward J.; Ott, Sascha; Lubitz, Wolfgang
Abstract A detailed characterization of a close synthetic model of the [2 Fe]H subcluster in the [FeFe] hydrogenase active site is presented. It contains the full primary coordination sphere of the CO‐inhibited oxidized state of the enzyme including the CN− ligands and the azadithiolate (adt) bridge, [((μ‐SCH2)2NR)Fe2(CO)4(CN)2]2−, R=CH2CH2SCH3. The electronic structure of the model complex in its FeIFeII state was investigated by means of density functional theory (DFT) calculations and Fourier transform infrared (FTIR) spectroscopy. By using a combination of continuous‐wave (CW) electron paramagnetic resonance (EPR) and hyperfine sublevel correlation (HYSCORE) experiments as well as DFT calculations, it is shown that, for this complex, the spin density is delocalized over both iron atoms. Interestingly, we found that the nitrogen hyperfine coupling, which represents the interaction between the unpaired electron and the nitrogen at the dithiolate bridge, is slightly larger than that in the analogous complex in which the CN− ligands are replaced with PMe3 ligands. This reveals, first, that the CN−/PMe3 ligands coordinated to the iron core are electronically coupled to the amine in the adt bridge. Second, the CN− ligands in this complex are somewhat stronger σ‐donor ligands than the PMe3 ligand, and thereby enable more spin density to be transferred from the Fe core to the adt unit, which might in turn affect the reactivity of the bridging amine.